Role of spacers in osmotic membrane desalination: advances, challenges, practical and artificial intelligence-driven solutions - Liang, Y. Y. (Elsevier, 2025)
Osmotic membrane desalination processes, including reverse osmosis (RO), forward osmosis (FO), pressure retarded osmosis (PRO) and osmotically assisted reverse osmosis (OARO) offer promising solutions for addressing water shortages. In these processes, spacers play a crucial role in enhancing flow dynamics and reducing fouling. This review provides a comprehensive analysis of advancements in spacer role for osmotic membrane desalination, focusing on CFD, 3D printing, monitoring strategies and AI-driven optimization. Both computational and experimental approaches for evaluating spacer effectiveness are examined. To maximize efficiency, novel spacer designs should prioritize mass transfer enhancement. Furthermore, enhancing osmotic membrane performance at the module scale requires optimizing spacer geometry and effective membrane length, such as tapered-array configuration to maintain higher cross-flow velocities and sustain mass transfer benefits. Key challenges involve balancing conflicting design objectives, considering system-level factors for improved performance, addressing manufacturing constraints and applying AI to optimize membrane spacers. Finally, this study provides strategies to bridge the gap between theoretical advancements and real-world implementation.